Small-volume plan optimization of inoperable early-stage centrally-located non-small-cell lung cancer using VMAT-based SBRT under the DIBH scenario: a single-arc model or a dual-arc plan? - Huang, Yangyang; Yuan, Jinjin; Chu, Alan; Yang, Jun; Liu, Yibao (Frontiers in Oncology, 2026)
IntroductionThis study aimed to comprehensively analyze the dosimetric parameters, plan complexity, gamma passing rates (GPRs), and most importantly, the beam-on time (BOT) of stereotactic body radiotherapy (SBRT) for small-volume inoperable early-stage centrally-located non-small-cell lung cancer (NSCLC) at a radiotherapy center. The analysis was based on both single-arc (SA) and dual-arc (DA) VMAT techniques under the deep inspiration breath hold (DIBH) scenario.MethodsWe retrospectively selected 24 cases of small-volume inoperable early-stage centrally-located NSCLC treated with SBRT under the DIBH scenario at our institution between March 2021 and June 2024. The redesigned SA-VMAT plans (SA plans) adopted the same prescription dose of 50 Gy/5 fractions and flattening-filter free (FFF) beam as the original DA-VMAT plans (DA plans). The 2-group plans (i.e., the SA and DA plans) were normalized to cover 95% of the planning target volume (PTV) and 99% of the gross tumor volume (GTV) by the prescription dose. The evaluation factors included PTV parameters (D98%, D2%, HI, CI, and R50%), organs at risk (OARs), plan complexity (segments and MUs), GPRs, and BOT.ResultsThe SA technique consistently yielded superior plans. Among the PTV parameters, the SA plans were superior to the DA plans in D98%, D2%, and HI (all p < 0.05), whereas the CI and R50% of the 2-group plans were comparable (all p > 0.05), and the SA plans had an increase in the ipsilateral PBT Dmax (p < 0.05). Otherwise, the differences between other OARs were insignificant (all p > 0.05). The SA plans had reduced complexity, with mean segments and mean MUs decreasing by 18.82% and 8.15%, respectively (all p < 0.001); the GPRs did not differ significantly under the three acquisition parameters (all p > 0.05). The mean BOT was reduced by 19.70% in SA plans (p < 0.001).DiscussionThe SA plans significantly shortened the BOT while maintaining comparable plan quality, thereby improving comfort for patients with small-volume inoperable early-stage centrally located NSCLC under the DIBH scenario. Future studies should accumulate more patient data to evaluate the long-term clinical outcomes of SA plans.